How Strategic Management Information Systems Drive Business Performance and Business Success ? - Jeffry Lim; Sebastian Sebastian; Junaidi Junaidi; Wenny Wenny; Eryc Eryc (Vifada Management and Social Sciences, 2024)
In the era of globalization, rapid business growth demands continuous innovation to maintain competitiveness and ensure long-term sustainability. Both formal and informal business sectors increasingly rely on management information technology as a strategic resource to enhance operational efficiency and achieve business success. This study aims to identify the key criteria for selecting appropriate management information technology, examine the inhibiting factors affecting its implementation, and formulate effective implementation strategies that support business performance. A descriptive research design was employed to provide a comprehensive overview of current practices in the adoption of management information technology across business organizations. Data were collected through systematic observation and analysis of relevant organizational practices and existing literature. The findings reveal that the successful implementation of management information technology is influenced by several critical factors, including technological compatibility, organizational readiness, human resource capabilities, and management commitment. Furthermore, inadequate infrastructure, resistance to change, limited technical expertise, and insufficient strategic planning were identified as major barriers to effective implementation. The study demonstrates that the application of well-planned and context-appropriate implementation strategies significantly enhances organizational effectiveness, supports informed decision-making, and improves overall business performance. These results underscore the importance of aligning technological initiatives with organizational goals and strategic planning. This research contributes to the growing body of knowledge on management information technology by providing practical insights for business managers and decision-makers seeking to leverage technology as a driver of sustainable business success.